Competitiveness of passenger and commercial vehicles sales in Malaysia between 2016 and 2017: constant market share analysis / Mohd Junaidi Razlan - Razlan, Mohd Junaidi (2020)
The Association of Southeast Asian Nations (ASEAN) countries have achieved rapid industrialization especially since the mid-1980s on Automotive Industry. Thus, automotive industry has been highlighted for the Gross Domestic Product (GDP) as well as Gross National Product (GNP) growth. The competitiveness between different brands in Passenger and Commercial vehicles are very stiff. The term of competitiveness is taken seriously in Malaysia for the purpose of sustainable development. Besides, to date there still does not exist a formal method of analyzing competitiveness of all brands in Passenger and Commercial vehicles. Therefore, this study is conducted to rank the passenger and commercial vehicle sales competitiveness in Malaysia between 2016 and 2017 by using the Constant Market Share (CMS) analysis. In addition, the other two specific objectives of this study are to determine the competitiveness of the national and non-national passenger and commercial vehicles sales in Malaysia and to analyse the performance of the sales of passenger and commercial vehicles in 2017 as compared to 2016. CMS Analysis is a simple analysis method normally used in analyzing competitiveness of exports between countries. This study proved that it also can be used in analyzing the competitiveness between brands in passenger and commercial vehicles. The data was collected from 10 brands of passenger and commercial vehicles where the results were run in Microsoft Excel. It shows that the most competitive in passenger vehicles for national brand was Proton while for non-national brand, the most competitive brand was Honda. The performance sales of passenger vehicle in year 2017 recorded an increment of 4,474 units. Furthermore, commercial vehicle is only dominated by non-national brands and the most competitive is Toyota brand.